Developing Empathy and Self-Regulation in Elementary School Students Through SEL-Based AR Learning - Fara Diba Catur Putri; Apriyanti Widiansyah (Ludi Litterarri, 2025)
The development of empathy and self-regulation in elementary school students is a major urgency in responding to the socio-emotional challenges of contemporary education. This study aims to explore the integration of Augmented Reality (AR) based on Social and Emotional Learning (SEL) as a transformative approach in shaping students' emotional skills. Using a qualitative method with a case study design, this study involved fourth-fifth grade students, teachers, and parents through observation techniques, semi-structured interviews, documentation, and exploratory questionnaires. The results show that the application of AR with interactive socio-emotional scenarios can stimulate empathy, increase self-awareness, and develop emotional regulation strategies through immersive experiences. AR acts as an affective medium that strengthens reflective and embodied learning, enabling students to experience and understand emotional dynamics in complex social situations. This study confirms that the effectiveness of AR-SEL learning is highly dependent on the quality of instructional design and teacher competence in facilitating socio-emotional values digitally. Therefore, support for educators' digital-affective literacy and the integration of a character-oriented curriculum are essential prerequisites. These findings conclude that the AR-SEL learning model has great potential to integrate cognitive and affective dimensions simultaneously in basic education.